Examining Students’ Motivation Towards Learning Science and Their Subject Experiences in Earth Science - Daniel S. Fernando; Mary Grace B. Bangcaya (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study examined the motivation towards learning science and experience in the Earth Science subject among students when considered as a whole and grouped by sex and academic performance. Additionally, it examined the differences in motivation towards learning science and experience in the Earth Science subject when grouped by demographics. Methodology: The study utilized a quantitative research design, particularly a descriptive comparative approach. The respondents were 115 randomly stratified sampled Grade 12 STEM students. A 35-item standardized questionnaire was used to assess students’ level of motivation and a 25-item adopted instrument was used to evaluate their subject experiences. Frequency count, percentages, Mean, Standard Deviation, Mann-Whitney U test, and Kruskal-Wallis H test were utilized. Main Findings: Hence, the students demonstrated a high level of motivation towards learning science. Likewise, the students reported a high level of experience in Earth Science, indicating that most perceived themselves as having engaged substantially. Meanwhile, the analysis revealed no significant differences in terms of sex for most motivational dimensions, except for the achievement goal. In terms of academic performance, the results showed there was no significant difference in performance goals. Additionally, there were no significant differences in the level of experience in the Earth Science subject based on the demographics. Novelty/Originality of this study: The study is novel as it may serve as valuable input for science teachers in enhancing Earth Science instruction. It may inform the development of more effective teaching strategies that foster students motivation and engagement in science learning.